ANALYSIS ON BIOCHEMICAL BASIS OF ROOT KNOT NEMATODE (MELOIDOGYNE INCOGNITA) RESISTANCE IN TUBEROSE GENOTYPES (POLIANTHES TUBEROSA) - P. RANCHANA; M. KANNAN; M. JAWAHARLAL (The Bioscan, 2015)
The study on biochemical constituents were carried out in the root of ten tuberose genotypes to select the genotype for hybridization which is resistance to root knot nematode infestation by inoculating the root knot nematodes artificially in the pot culture experiment. The study revealed that among the genotypes, the roots of Kahikuchi Single resulted with the highest level of phenol (19.84 mg g-1), ortho-di-hydroxy phenol (15.84mg g-1), peroxidase (3.65 OD min-1 g-1), polyphenol oxiase (3.58 OD mg g-1), phenylalanine ammonia lyase (16.10nmol of trans cinnamic acid min-1 g-1) and acid phosphatase activity (131.88m moles p-nitrophenol min-1 mg-1 protein) at 96 hours after inoculation. Hence, it is suggested that the genotype Kahikuchi Single could be used as one of the parent to develop hybrids.